О питании дроздов в Южном Приморье - Нечаев, В.А.; Назаров, Ю.Н. (Вестник зоологии, 1968)
The data on the nourishment of eight species of thrushes are presented on the basis of examining 1'34 stomaches. The thrushes were collected mainly on islands in the Bay of Peter the Great, in upper reaches of the river Maikha (vil. Peishula) and in the valley of the river Pachikhesa (station Kiparisovo).